Investigating Soil Adhesion and Antiadhesion Performance of Nonsmooth Subsoiler Surfaces - Jinguang Li; Hongyan Qi; Yunhai Ma; Peng Gao; Baoguang Wu (Journal of Engineering)
Soil adhesion is one of the main factors affecting the working resistance and energy consumption of agricultural machinery. Many scholars have been doing much research on the method of soil antiadhesion, but the conditions for the occurrence of adhesion need to be further discussed. By measuring and comparing the repose angle and external friction angle of the soil, this paper discussed the influence of soil texture and soil water content on soil adhesion. It was found that when the soil moisture content was less than 20%, the cohesive soil showed weak adhesion. When the soil moisture content was more than 20% and lower than the soil liquid limit, the cohesive soil shows strong adhesion. When the soil shows strong adhesion, the nonsmooth convex structure on the surface of the subsoiler has a good desorption effect. Notably, in clay loam with a 30% moisture content, the average tillage resistance of a subsoiler with convex structures was 15.13% lower compared to a smooth-surfaced subsoiler.